Model-based optimisation of CT imaging parameters for dimensional measurements on multimaterial workpieces. Issue 1 (2018) - Schmitt, Robert H.; Buratti, Andrea; Grozmani, Natalia; Voigtmann, Christoph; Peterek, Martin
Abstract: The uncertainty of measurements with X-ray computed tomography (CT) depends on setup parameters that the operator must choose. Currently, there is no established model describing the relationship between setup parameters and measurement uncertainty. This paper presents an analytical method for optimising CT setup parameters for dimensional measurements on multimaterial workpieces. The method is based on defining and maximising scan quality. An experimental study proved the validity of the method by analysing the standard deviation of CT measurements on a multimaterial test artefact. An analysis of variance on the uncertainty contributions showed that the predicted parameters were globally optimal.